Predicting learnersa agility and readiness for future learning ecosystem - Ab Jalil, Habibah; Ismail, Ismi Arif; Ma’rof, Aini Marina; Lim, Chee Leong; Hassan, Nurhanim; Che Nawi, Nur Raihan (MDPI, 2022)
Agility and future readiness are fundamental 21st-century skills that could guide university students globally to thriving and benefiting from a VUCA—volatile, uncertain, complex, and ambiguous—world. The ability to respond flexibly, make informed decisions, and adapt to rapid change reflects future-readiness capabilities. However, little is known about the empirical role of the university curriculum, learning ecosystem, and learning experience as perceived by university students in developing these skills. Therefore, we analysed data collected from 209 Malaysian university students from 16 universities to assess whether these three pertinent factors impact the students’ learning agility and determine how well learning agility predicts learners’ future readiness. The present study empirically assessed a theoretical model using a partial least squares structural equation modelling (PLS-SEM) approach. The analysis supported all the hypotheses proposed in this study, which implies that the extended model could effectively predict learners’ agility and future readiness. The results revealed that the university learning experience, ecosystem, and curriculum positively, directly, and significantly affected learning agility and future readiness. Furthermore, the findings showed that student agility significantly mediated the relationships between the student learning experience, university learning ecosystem, and curriculum and student future readiness. Taken together, these results highlight the importance of a future-ready education nurtured by a vibrant learning ecosystem that delivers lasting values and experiences for students and communities to appreciate the opportunities for a challenging yet exciting future offered by a VUCA environment. The established empirical model describing the empirical interplays between these correlates could, in turn, aid better evidence-based policy making in higher education.